Folgen eines höheren CO₂-Preises in der EU – wer gewinnt, wer verliert?; Consequences of a igher carbon price in the EU: Who will win, who will lose? - Hendrik Mahlkow; Thieß Petersen; Joschka Wanner (Wirtschaftsdienst, 2021)
Damit die EU ihre ambitionierten Klimaschutzziele erreichen kann, werden die Preise für Treibhausgasemissionen in den nächsten Jahren spürbar steigen. Das hat ökonomische Auswirkungen für die EU-Mitgliedsländer, aber auch den Rest der Welt. Einzelne Sektoren und auch Volkswirtschaften werden davon unterschiedlich stark getroffen. – – If the EU is to achieve its ambitious climate protection targets, prices for greenhouse gas emissions will rise noticeably in the next few years. This has economic implications not only for the EU member countries, but also for the rest of the world. This article presents the results of simulations covering 141 countries/regions and 65 economic sectors. The economic impact of the EU increasing its carbon price by 50 is calculated. In addition to the effects on real GDP and sectoral production, the consequences for the volume of emissions are also calculated. The carbon price increase is found to effectively bring down emissions, though with non-negligible leakage effects and at very heterogenous costs, both across countries and across sectors.
Keywords: F18; Q54; Q56; 330; Treibhausgas-Emissionen; Klimaschutz; Klimapolitik; Bruttoinlandsprodukt; Wertschöpfung; EU-Staaten